A set of primers for the amplification of chloroplast microsatellites in Quercus (Molecular Ecology Notes, 2003)
The increase in demand for the certification of oak seed lots, as well as control of the geographical origin of oak wood, has led us to develop powerful genetic markers permitting us to discriminate among provenance regions. With the aim of detecting new chloroplast variants, we have identified 17 potential cpSSRs motifs from available oak sequences and tested their variability among French oak populations. Six loci were polymorphic at the intraspecific level in Quercus petraea and Q. robur. Moreover, conservation of the primer pairs was checked on a set of 21 forest tree species and they were all shown to work well on several Quercus species, and even within Fagacaea.